Product service system with inventory control for production line of a metal industry - Farah Ameelia, Mohammad (2024)
The development of Product Service Systems (PSS) allowed traditional manufacturing companies to capitalise on increased profits from this dynamic market by integrating products and services. Manufacturing companies must prioritize inventory control to reduce expenses, meet customer demands, and gain a competitive edge by incorporating product and service controls into their operations. This study seeks to investigate PSS by developing a comprehensive inventory control model that focuses on the production line of the metal market industry. The implementation of inventory control in PSS introduces numerous uncertainties, such as supply capacity disruptions, yields, capacity demands, and variable replenishment lead times, necessitating a globally recognized standard approach for efficient management. This research identifies PSS transitions from the sale of tangible goods to the provision of diverse products and services. The Integrated Definition for Function Modelling (IDEFØ) model encompasses the entire process and aids in comprehending the behaviour of the system. This research presents findings related to the development of standard operating procedures (SOP). This research contribution has important implications for researchers and practitioners; it provides insights into improving PSS inventory control strategies. Incorporating these strategies into inventory control policies enables manufacturers to effectively manage uncertainties and enhance overall performance in their PSS.